2004
DOI: 10.1074/jbc.m309579200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of p21-Activated Kinase 4 with PDZ-RhoGEF, a G Protein-linked Rho Guanine Exchange Factor

Abstract: RhoGTPases regulate a wide variety of cellular processes, ranging from actin cytoskeleton remodeling to cell cycle progression and gene expression. Cell surface receptors act through a complex regulatory molecular network that includes guanine exchange factors (GEFs), GTPase activating proteins, and guanine dissociation inhibitors to achieve the coordinated activation and deactivation of Rho proteins, thereby controlling cell motility and ultimately cell fate. Here we found that a member of the RGL-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 34 publications
(45 reference statements)
3
46
0
Order By: Relevance
“…This is also consistent with our findings that PAK4 kinase activity leads to dissolution of stress fibers through phosphorylation of GEF-H1 in NIH-3T3 cells. Our findings related to antagonism of GEF-H1-dependent Rho activity, which is dependent upon PAK4 recruitment and kinase activity, are consistent with recent studies showing that PAK4 can antagonize Rho activity through direct interaction with RhoGEF (Barac et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
“…This is also consistent with our findings that PAK4 kinase activity leads to dissolution of stress fibers through phosphorylation of GEF-H1 in NIH-3T3 cells. Our findings related to antagonism of GEF-H1-dependent Rho activity, which is dependent upon PAK4 recruitment and kinase activity, are consistent with recent studies showing that PAK4 can antagonize Rho activity through direct interaction with RhoGEF (Barac et al, 2004).…”
Section: Discussionsupporting
confidence: 79%
“…Instead, these two proteins have a positive functional interaction in S. pombe cells: gain of Rga8 function exacerbates phenotypes caused by gain of Rho1 function and vice versa, and both Rho1 and Rga8 antagonize Pak1 function . This linkage between a member of the Pak family and a regulator of Rho is not unique to fission yeast, because two groups have recently reported that both group A and group B mammalian Paks phosphorylate and thereby alter the localization and/or activity of additional Rho-GEFs (Barac et al, 2004;Zenke et al, 2004).…”
Section: Pak1/shk1mentioning
confidence: 99%
“…Expression of activated Pak4 in fibroblasts decreases adhesion to the extracellular matrix and promotes proliferation, leading to anchorage-independent growth and increased cell migration (Callow et al, 2002;Qu et al, 2001). Pak4 substrates include the cytoskeletal regulatory kinase LIMK1, the pro-apoptotic protein BAD and probably PDZRho-GEF (Barac et al, 2004;Dan, C. et al, 2001;Gnesutta et al, 2001).…”
Section: Group B Paksmentioning
confidence: 99%
“…These GEFs may then interact through other regions with membrane components, such as membrane phospholipids through their PH domain, thus either causing a conformational change in the DH domain that then becomes activated, or adopting an orientation with respect to the lipid bilayer that facilitates the interaction of the DH domain with membrane-bound Rho. This membrane interaction might be also required for the regulatory properties of tyrosine or serine/threonine protein kinases that modulate RGL-RhoGEFs, such as focal adhesion kinase and PAK4 (21,37), respectively. These, as well as other possibilities are under current investigation.…”
Section: Figmentioning
confidence: 99%